2016
DOI: 10.15288/jsad.2016.77.121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Residence, School Status, Work Status, and Social Influence on the Prevalence of Alcohol Use Among Emerging Adults

Abstract: ABSTRACT. Objective:The fi rst year after high school is a transitional year, with increased independence from parental supervision, contact with other independent youth, and exposure to new environments, all of which may infl uence substance use. This article reports longitudinal predictors of change in the prevalence of alcohol use and heavy episodic drinking among adolescents and environmental correlates (i.e., residence, college attendance, and work status) with drinking the year after high school. Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 51 publications
3
42
1
6
Order By: Relevance
“…Consequently, a variety of recently published studies have demonstrated that frequently spending time with friends, having friends who drink, or drinking with friends is a major risk factor for binge drinking (Dietze, Livingston, Callinan, & Room, 2014;Eisenberg, Golberstein, & Whitlock, 2014;Elisaus et al, 2015;Hahm, Kolaczyk, Jang, Swenson, & Bhindarwala, 2012;Harakeh et al, 2012;He, Assanangkornchai, Cai, & McNeil, 2016;Kelly et al, 2016;Kuntsche, Otten, & Labhart, 2015;Mustonen, Makela, & Lintonen, 2016;Scholly, Katz, & Kehl, 2014;Seid, Hesse, & Bloomfield, 2016;Simons-Morton et al, 2016;Soloski et al, 2016;Song et al, 2012;Stickley et al, 2013;Tomczyk, Isensee, & Hanewinkel, 2015;Washburn, Capaldi, Kim, & Feingold, 2014).…”
Section: Social Factors (Ii): Peersmentioning
confidence: 99%
“…Consequently, a variety of recently published studies have demonstrated that frequently spending time with friends, having friends who drink, or drinking with friends is a major risk factor for binge drinking (Dietze, Livingston, Callinan, & Room, 2014;Eisenberg, Golberstein, & Whitlock, 2014;Elisaus et al, 2015;Hahm, Kolaczyk, Jang, Swenson, & Bhindarwala, 2012;Harakeh et al, 2012;He, Assanangkornchai, Cai, & McNeil, 2016;Kelly et al, 2016;Kuntsche, Otten, & Labhart, 2015;Mustonen, Makela, & Lintonen, 2016;Scholly, Katz, & Kehl, 2014;Seid, Hesse, & Bloomfield, 2016;Simons-Morton et al, 2016;Soloski et al, 2016;Song et al, 2012;Stickley et al, 2013;Tomczyk, Isensee, & Hanewinkel, 2015;Washburn, Capaldi, Kim, & Feingold, 2014).…”
Section: Social Factors (Ii): Peersmentioning
confidence: 99%
“…Longitudinal sampling weights were used to reflect the population‐based sampling and to correct for nonresponse in the questionnaire. Simons‐Morton et al studied how drinking behavior was associated with environmental and social influence using the GEE transition model with exchangeable working correlation. The transition model we considered in this paper was similar but had fewer covariates, for illustrative purposes.…”
Section: Application To Next Generation Health Studymentioning
confidence: 99%
“…In our application, interest is in estimating the propensity toward either initiating consumption (0‐1, transition) or continuing consumption (1‐1, transition) of alcohol. Simons‐Morton et al examined various risk factors for this one‐year transition probability. They employed a GEE approach assuming a first‐order lagged dependence with an independence variance structure.…”
Section: Introductionmentioning
confidence: 99%
“…Substance use is a major public health problem for adolescents and young adults in the United States, and college students have their own particular set of risks for use and barriers to treatment [1,2]. Of an estimated 9 million full-time college students in 2014, approximately 10% reported initial use in the past year of alcohol and 6% reported initial use of illicit drugs (including marijuana, which accounted for the vast majority of this category; [3]).…”
Section: Introductionmentioning
confidence: 99%